Expectant management versus termination of pregnancy in preterm premature rupture of membranes at 34 to 36+6 weeks gestation: a randomised control trial - Kaur, Amanjot; Jain, Vanita; Bagga, Rashmi; Radhika, S.; Venkataseshan, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This research work aimed to study the effect of expectant management till 37 weeks on various maternal and neonatal outcomes in comparison delivery at 34 weeks in pregnant women with pPROM. Methods: All pregnant women presenting to our tertiary care institution with pPROM at a viable gestational age fulfilling the inclusion and exclusion criteria were managed conservatively till 37 weeks. The maternal and neonatal outcomes were noted and compared with women with pPROM who delivered at 34 weeks of gestation. Results: There is no significant increase in the neonatal or maternal sepsis in the patients with preterm premature rupture of membranes managed conservatively beyond 34 weeks period of gestation. Two third of the patients managed conservatively had spontaneous onset of labor thereby reducing the complications of induction of labor. In addition, 44% of patients managed expectantly gained >5 days of maturity beyond 34 weeks. Conclusions: Expectant management of pPROM beyond 34 weeks period of gestation may be an alternative to immediate delivery.